Green Entrepreneurship, Corporate Finance & Western Balkans in the Post-Pandemic World: Sustainable, Green and Scalable Investments in the Post COVID-19 Era - , Vasiliki A. Basdekidou (Archives of Current Research International, 2021)
The disruption of the recent COVID crisis has as a result many and serious environmental, social, political, and economic consequences. In the entrepreneurship domain, now it is the time for reimagining the relationship between people (employees, customers) and technology. This is very important in the so-called Western Balkan (WB) countries, apply for EU membership whilst facing serious environmental, social, political, economic and governance problems. The disruptions brought by the COVID-19 pandemic crisis have made WB countries and a number of international and domestic companies think about increasing the resilience of their production through sustainable, green, and scalable investments and management (e.g. supply diversification, geographically closer to customers activities and delivery centers, shorter supply chains, smarter solutions, thoughtful initiatives, increased home production, smart scalable inventories, open governance, new technology transformation, adaptable management, trusted relations, etc.). The main target of this article was to perform a practical primitive analysis of access to economic and green entrepreneurship constraints in the WB region and in the post COVID-19 pandemic crisis times. Hence, in this article, several green entrepreneurship perceptions, financial and green investment initiatives, operated as financial constraints, which should form in WB countries just after the COVID crisis introduced and discussed. Particularly, the factors that influenced these perceptions/initiatives/constraints, and the consequences should they had on the political, social, and economic dynamics in WB were presented in this paper. The main article’s objectives are the following: (i) to analyze how the WB economies could benefit from these initiatives after the COVID-19 pandemic crisis; and (ii) to form the suitable environmental, social, economic, and governance commitments. Findings and proposed entrepreneurship analysis is complemented, in Section 4, by a review of the environmental, social, and governance commitments (operating as nine “financing constraints” with great corporate finance functionalities), which should operate (in the post COVID-19 era) as economic reform by national authorities in Western Balkan countries, through specific EU programmes and various green entrepreneurship and corporate finance initiatives. For instance, four key findings were recorded in the commitment “Environmental issues”. The results of the presented research, as recommendations, were referred to the adoption of good and innovative practices for sustainable green entrepreneurship in WB. In particular, the relationship between people (employees, customers) and the new technology was discussed and documented, as well as the issue of “digital transformation in the WB entrepreneurship” by identified nine (9) commitments that fully or partially support green entrepreneurship; the concept of “team-work collaboration” (collaborative entrepreneurship and solutions); and the “geospatial optimization” initiative (e.g. geospatial optimization for delivery centers) were introduced, analyzed and documented.